(3EOGQI GdCYeGd GdOhdjI (B/s - (3OjQj, RGgO eMeOs ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2011)
(3ebOeI aj GOGQI GdGYeGd GdOhdjI , LOhi GdGSJKeGQGJ GdGLfHjI (B: (3JMdjd dhLgGJ GdfXQ GdHOjdI h OhQ GdTQcGJ eJYOOI GdLfSjGJ , GSJQGJjLjI GOGQI GdehGQO GdHTQjI GdOhdjI h eJYOOI GdLfSjI , GdGOGQI GdGdcJQhfjI ddehGO GdHTQjI aj Xd GdCYeGd GdOhdjI , GSJQGJjLjGJ GdTQcGJ GdJcfhdhLjI YGHQI GdbGQGJ , JfXje h JhLjg GdGSJKeGQGJ GdCLfHjI (B: (3GdSjGSGJ h GdGLQGAGJ h GdMhGaR aj GdOhd GdeVjaI , eaghe GdYhdeI h JWhQgG h eOi bHhdgG , GdGSJKeGQ GdGLfHj GdeHGTQ h GdJNWjW GdGSJQGJjLj , GdJcJdGJ h GdGMdGa GdGSJQGJjLjI GdchfjI , GdHjFI GdSjGSjI GdOhdjI h GdHjFI GdGbJUGOjI h GdKbGajI h GdGLJeGYjI h GdbGfhfjI , GdJLGQI GdOhdjI , ejRGf GdeOahYGJ h CSYGQ GdYedGJ , GOGQI GdGYeGd GdOhdjI GdYcSjIs
Keywords: (3EOGQI GdCYeGds; (3GdTQcGJ GdeJYOOI GdLfSjIs